Analisis Economic Value Added (EVA) Perusahaan Sektor Energi di Bursa Efek Indonesia Periode 2013-2022 - Akhmad Fauzan Des Putra; Isnurrini Hidayat Susilowati; Ratnawaty Marginingsih; Wiwik Widiyanti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The Energy sector is one of the sectors in the Indonesian economy and the Indonesia Stock Exchange (IDX). 86 companies listed on the IDX. The sample is to 7 companies. The purpose of the study was to determine the Financial Performance Analysis of Energy sector companies listed on IDX for the period 2013-2022 using Economic Value Added (EVA). Based on calculations, EVA ADRO negative results (EVA<0) in 2013-2015 and 2020, positive EVA (EVA>0) in 2016-2019 and 2021-2022. AKRA's EVA from 2013-2022 are all positive (EVA>0). EVA HRUM in 2014-2015 was negative (EVA <0), in 2016-2023 EVA was positive (EVA>0). EVA ITMG from 2013-2022 are all positive (EVA>0). EVA MEDC in 2013-2021 is negative (EVA <0) and 2022 is positive (EVA>0). PGAS EVA in 2013-2014 was positive (EVA>0) and 2015-2023 was negative (EVA<0). PTBA's EVA from 2013-2022 are all positive (EVA>0). EVA>0 indicates the rate of return generated from company is greater than the cost of capital or it has succeeded in creating added value in that year. EVA<0 indicates the company's value has decreased or decreased where the rate of return is lower than the cost of capital it means fails to create the added value demanded by investors.